ESTIMATION OF THE MAIN GAS PIPELINE OPERATION UNDER EMERGENCY CONDITIONS OF GAS LEAKAGE - Bolonny, V. T. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The characteristics of the gas transportation system of Ukraine are presented, the emergency risks of domestic gas transportation pipeline systems are established. The analysis of the accident rate of gas pipeline transport in Ukraine and Russia was carried out. Presented technique of determining the emergency pressure in the pipeline, depending on the amount of gas losses from pipeline at the point of its leakage provides an opportunity to determine the volume of gas losses from the pipeline and to evaluate the environmental risks due to emergency situations of gas pipeline transport. This technique makes it possible to calculate the pressure at each point of pipeline under nonstationary conditions caused by changes in pressure at the beginning and at the end of the sector and the emergence of concentrated gas leakage. Based on the results of calculations, a graph of pressure change of the oscillatory process in the gas pipeline caused by jump of pressures at the beginning and at the end of the sector, and the presence of probable leakages at the determined point of the trace was constructed. The linear part of the main gas pipelines is the most dangerous object, as all emergency situations are associated with emergency processes of different intensity in the form of gas leakage into the environment and in fact are dangerous when system failures appear. The process and the time period for the formation of the gas pollution zone depend on the amount of gas leakage, its intensity and depth of the gas pipeline. The filtration resistance of the soil as a porous medium, in particular its permeability, have a significant effect on the amount of gas leakage through corrosive orifice. As a result, there is a correlation between the amount of gas losses associated with the leakage, and the laws of its filtration in the surrounding soil. As a result, the effect of gas filtration process in the soil in the event of leakage from pipelines has been investigated. The graphic dependence of change in pressure of the filtration resistance of the medium and the time-changing leakage which are designed for different soil characteristics is obtained.